PEMBERDAYAAN PEJABAT STRUKTURAL KEPEGAWAIAN PEMERINTAH TERHADAP PRODUKTIVITAS KERJA YANG BERMUTU: Kasus dalam Bidang Kepegawaian di Provinsi DKI Jakarta dan Provinsi DI Yogyakarta - Djoko Sutrisno; Sumardjo Sumardjo; Pang S Asngari; Soedijanto Padmowihardjo; Prabowo Tjitropranoto (Jurnal Penyuluhan, 2006)
The civil service management was changed of paradigm to some extent, that is appointment of the personnel of government structural officials (PSOG) is carried out based on profesionalisme principle. Although in implementation, work achievement of the personnel of goverment structural officials (PSOG) indicate is still unsatisfying. This research objectives are: (1) to evaluate the level of empowerment, internal characteristics of organization, motivation, and competency of PSOG; (2) to decide the determinant factors that influence the empowerment, competence, and motivation of PSOG; (3) to formulate the model to increase competency of the personnel of government structural officials (PSOG). Location of the research are in DKI Jakarta and DI Yogyakartaof which 14 government offices were selected as study sites From the analysis of data obtained the scores as follow: (1) Level of empowerment, attitudes, motivation, and competency with category good. Level of non formal education (seminar, discussion and workshop) and organization technology with category good. Level of works experience with category not good; (2) The factors of non formal education (seminar, discussion and workshop), attitudes and organization technology is significantly influence the empowerment of PSOG; (3) The factors of empowerment and motivation of PSOG significantly influence competency; (4) The factor of empowerment of PSOG is significantly influence the motivation of PSOG.